2016
DOI: 10.1111/corg.12154
|View full text |Cite
|
Sign up to set email alerts
|

Looking Inside the Black Box: The Effect of Corporate Governance on Corporate Social Responsibility

Abstract: Manuscript Type: ReviewResearch Question/Issue: This study provides a systematic multi-level review of recent literature to evaluate the impact of corporate governance mechanisms (CG) at the institutional, firm, group, and individual levels on firm level corporate social responsibility (CSR) outcomes. We offer critical reflections on the current state of this literature and provide concrete suggestions to guide future research. Research Findings/Insights: Focusing on peer-reviewed articles from 2000 to 2015, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
505
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 407 publications
(531 citation statements)
references
References 223 publications
(242 reference statements)
21
505
0
5
Order By: Relevance
“…Secara lebih spesifik kajian mengenai karakteristik dewan direksi menjadi penting. Karakteristik dewan direksi tersebut mencakup diversitas dewan (Muttakin, Khan, dan Subramaniam, 2015) seperti keberadaan perempuan dalam dewan direksi (Fuente et al, 2017;Huang, 2013;Jain dan Jamali, 2016), lama menjabat (Huang, 2013;Lewis, Walls, dan Dowell, 2014;Rao dan Tilt, 2016a), keberadaan direktur asing (Barka dan Dardour, 2015;GarciaSanchez, Cuadrado-Ballesteros, dan Sepulveda, 2014) dan ukuran dewan (Fuente et al, 2017;Jain dan Jamali, 2016).…”
Section: Pendahuluanunclassified
“…Secara lebih spesifik kajian mengenai karakteristik dewan direksi menjadi penting. Karakteristik dewan direksi tersebut mencakup diversitas dewan (Muttakin, Khan, dan Subramaniam, 2015) seperti keberadaan perempuan dalam dewan direksi (Fuente et al, 2017;Huang, 2013;Jain dan Jamali, 2016), lama menjabat (Huang, 2013;Lewis, Walls, dan Dowell, 2014;Rao dan Tilt, 2016a), keberadaan direktur asing (Barka dan Dardour, 2015;GarciaSanchez, Cuadrado-Ballesteros, dan Sepulveda, 2014) dan ukuran dewan (Fuente et al, 2017;Jain dan Jamali, 2016).…”
Section: Pendahuluanunclassified
“…With this in mind, the link between board composition and CSR reporting is given emphasis throughout, even though such an explicit research framework does not exist in the literature so far. We have relied on a broad research structure suggested by Jain and Jamali (2016). An analysis of multilevel corporate governance mechanisms implies that there are institutional-level, firm-level, group-level, and individual-level corporate governance mechanisms.…”
Section: Board Composition and Csr Reporting Frameworkmentioning
confidence: 99%
“…The adoption of the Directive 2014/95/EU in the European member states has great implications for board diversity and CSR reporting (Federation of European Accountants, 2015; Johansen, 2016; Monciardini, 2016), as specific PIEs must prepare a non-financial declaration and a diversity report as part of the corporate governance statement. The relationship between board composition and CSR reporting is also a growing topic of empirical research from an international perspective (Jain and Jamali, 2016;Malik, 2015). Prior empirical research has focused on the link between board composition variables such as internal corporate governance and measures of CSR reporting and, over the last few years, a growing number of studies have been carried out that have incorporated a statistical examination of the impact of specific board composition variables (e.g., gender diversity) on the quality and quantity of CSR reports .…”
Section: Introductionmentioning
confidence: 99%
“…However, CSR can also be strategic whereby it can combine economic and social benefits (Husted and Salazar [43]). Jain and Jamali [44] argue that the outside-in ap- Attracting and retaining human resources is central for the success of an organisation. Companies with high corporate social performance are more appealing to job seekers that those with low CSP (Albinger and Freeman [45]) and companies with good social credentials have better employee retention rates (Peterson [46]).…”
Section: Does the Csr Levy Results In Competitive Disadvantage?mentioning
confidence: 99%